PENGARUH PENERAPAN SISTEM E-FILING, E-BILLING DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WPOP DI KABUPATEN NGANJUK - Wahyuni, Sri; Faisol, Faisol; Sugeng, Sugeng (Universitas Nusantara PGRI Kediri, 2023)
The background of this research is that there has been a continuous downward trend in the level of taxpayer compliance in Nganjuk Regency in the last four years. This is important for further scrutiny and research. Therefore, the aim of the research is to determine the effect of the E- Filling system, E-Billing System, and knowledge of taxation on individual taxpayer compliance, both socially and simultaneously in Nganjuk Regency. This research uses the quantitative approach. Sample which is used in this study covers 100 individual taxpayers who are domiciled in Nganjuk Regency and analyzed using multiple linear regression with SPSS software for Windows version 23. The result found that (1) the E-filling system has a positive effect on individual taxpayer compliance. (2) E-Billing System has no effect on individual taxpayer compliance. (3) Tax knowledge has a positive effect on individual compliance. (4) Simultaneously, E- Filling system, E-Billing system, and tax knowledge have a positive effect on individual taxpayer compliance. The findings of this study are expected to expand previos research, namely adding new information and presenting a comprehensive review of the taxpayer compliance framework in the field of academic research.